2007
DOI: 10.1590/s1413-70542007000400045
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética de isolados do cogumelo Agaricus blazei por meio de marcadores RAPD

Abstract: RESUMOAgaricus blazei (Murrill) ss. Heinem. é um cogumelo nativo do Brasil que vem despertando a atenção de vários pesquisadores em todo o mundo, devido às suas propriedades farmacológicas e nutricionais. Este trabalho teve por objetivo, analisar a variabilidade genética de alguns isolados utilizados comercialmente, por meio de marcadores RAPD. Foram analisados nove isolados de A. blazei, provenientes de diferentes regiões do Brasil e, como controle, dois isolados de A. bisporus. Todos eles fazem parte da cole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Brazil is the world's largest producer of sun mushrooms (Agaricus blazei Murrill), which is a native species, with favorable climatic conditions in Brazil for its cultivation (Tomizawa, et al, 2007). Some edible mushrooms, including sun mushroom, have important therapeutic properties and have been traditionally used in oriental medicine (Taveira;Novaes, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is the world's largest producer of sun mushrooms (Agaricus blazei Murrill), which is a native species, with favorable climatic conditions in Brazil for its cultivation (Tomizawa, et al, 2007). Some edible mushrooms, including sun mushroom, have important therapeutic properties and have been traditionally used in oriental medicine (Taveira;Novaes, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…subrufescens mushrooms exhibit a high level of polymorphism in the ITS of the nuclear rDNA region (Kerrigan et al, 2005 Our results revealed that all the A. subrufescens strains characterized here were phylogenetically related to the Americas/Europe specimens, bearing an ITS of type A (ABL 16/01) or both types A and B (ABL 18/01, ABL 98/11, and ABL CS7). A previous study carried out with other strains and molecular markers showed that the strains used in Brazil had substantial genetic similarity (Tomizawa et al, 2007), suggesting a common origin. Thus, any differences in agronomic traits among these strains should be related to other genomic regions that may be assessed by various molecular methods such as simple sequence repeat (SSR) markers, which are potentially useful as a molecular tool to study genetic diversity and reproductive biology (Foulongne-Oriol et al, 2012.…”
Section: Discussionmentioning
confidence: 94%
“…Li et al 42 , em que ratas grávidas receberam um extrato aquoso de A. bisporus por 15 dias, o A. blazei e A. bisporus, que pertencem ao mesmo gênero e possuem grau de similaridade genética de 3% 43 .…”
Section: Estes Resultados Corroboram Com O Estudo Deunclassified